2008
DOI: 10.1007/bf03175319
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and identification of dominant microorganisms involved in naturally fermented goat milk in Haixi region of Qinghai, China

Abstract: Based upon morphological, physiological and biochemical analysis, 33 strains of lactic acid bacteria were isolated and identified from 11 samples of traditional natural fermented goat milk collected from different individual households in Haixi region of Qinghai. The counts of lactic acid bacteria were 2.5 x 108ෂ3.0 x 10 9 CFU/mL, while yeasts were 2.6 x 10 6 ෂ1.6 x 10 8 CFU/mL. Strains were identified as follows: 7 strains of Lactobacillus delbrueckii subsp. lactis, 4 strains of Lactobacillus delbrueckii subs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 28 publications
0
16
0
Order By: Relevance
“…Previous studies showed that LAB is the dominant species in the microorganisms of Qula cheese, and play the most important role in the accumulation of nutrients (Bao et al, 2012;Duan et al, 2008). Some of the lactic acid bacteria are also known to have beneficial effects on human health (Mohd Adnan and Tan, 2007;Zhang, W. Y. et al, 2008). Because of its specific flavor, rich nutrients, and smooth texture, Qula is popular among the local consumers, which is proven by its constant presence in the local markets.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies showed that LAB is the dominant species in the microorganisms of Qula cheese, and play the most important role in the accumulation of nutrients (Bao et al, 2012;Duan et al, 2008). Some of the lactic acid bacteria are also known to have beneficial effects on human health (Mohd Adnan and Tan, 2007;Zhang, W. Y. et al, 2008). Because of its specific flavor, rich nutrients, and smooth texture, Qula is popular among the local consumers, which is proven by its constant presence in the local markets.…”
Section: Introductionmentioning
confidence: 99%
“…LAB isolates were tested for NH 3 production from arginine, nitrate reduction, motility, dextran production, gas production from glucose, salt tolerance, growth temperature and pH ranges (Kozaki et al, 1992;Zhang et al, 2008). The presence of meso-DAP in the bacterial cell wall was determined with reference to the schemes outlined by Mathara et al (2004).…”
mentioning
confidence: 99%
“…mIol fermentation tests were performed with all the analyzed strains as described by Zhang et al (2008).…”
Section: Methodsmentioning
confidence: 99%